Kecantikan, Skincare, dan Validasi Sosial - Iftita, Nur (Emik, 2025)
Facial skincare has become a cultural practice that serves not only as a functional necessity but also as a means of seeking social validation. Although most research on beauty focuses on purchasing decisions and marketing effectiveness, the role of social validation in shaping consumer experiences and satisfaction with skincare products has not been widely explored, and this article fills this gap. Using a qualitative approach, this study involves ten informants consisting of two housewives, three content creators, two make up srtists and college students respectively, and a high school student. Their age ranges between 17 and 27 years, and they are active users of Bening's Skincare in Makassar. Data collection was conducted by combining observation on social media platforms and in-depth interviews. The study shows that consumer perceptions are formed through two main aspects:  expectations influenced by visual testimonials on social media and interpersonal recommendations, and safety perceptions that become critical considerations, especially after the "blue label" controversy. Three main factors influence product selection: recommendations from close friends/relatives that provide interpersonal trust, the influence of social media that provides visual evidence and social proof, and suitability to personal needs based on individual skin conditions. Social validation plays a significant role in mediating between individual needs and social expectations. It operates through three dimensions; recognition through appearance transformation, social feedback, and social pressure. Positive validation occurs when the environment provides affirming responses such as compliments and positive attention, while negative validation occurs by critical responses from other or by comparison between those who have good-looking skin condition and who have bad-looking skin condition that create pressure to improve skin conditions. Consumers know they are being validated through direct comments, changes in social interactions, engagement on social media, and comparisons with others in their social circle. It is argued in this article that skincare consumption is not solely based on functional needs, but is also shaped by complex social dynamics, where consumers negotiate their identity amid beauty standards mediated by social media and pressures to maintain appearances that align with social expectations.